Axonal neuropathy and hearing loss associated with alpha interferon treatment in chronic hepatitis B: A case report - Ayşe TUNCA; Mustafa ERBAYKAK; Şirin AYTAÇ; Cansel TÜRKAY (Turkish Journal of Gastroenterology, 2019)
-